HE CULTURAL BACKGROUND BETWEEN TRADITIONAL VALUE PERCEPTIONS OF WORKING WOMEN AND THE CONCEPT OF GENDER IN ALGERIAN INSTITUTIONS - Atika DJAIDJA (Ziglôbitha)
Abstract: Women have taken the initiative to enter the field of leadership, which comes with its own difficulties and risks, as a strategy to change their reality and the reality of those close to them. By doing so, they have taken a step towards risk and challenge, using various theoretical and technical knowledge they possess on one hand, and their personal reservoir composed of their characteristics, hobbies, inclinations, aspirations, and values acquired since childhood on the other, all to achieve social advancement.